Development and designing a folding bicycle stand / Raja Imran Hakimi Raja Ahmad Shukri and Hazim Sharudin - Raja Ahmad Shukri, Raja Imran Hakimi; Sharudin, Hazim (School of Mechanical Engineering, 2023)
The invention of a bicycle stand is far from recent, but the implementation of innovative improvements towards the idea is still within reach. One operating principle of these stands is based on lifting the bicycle off the ground and clamping the stays of the bicycle to the stand, so the rear frame of the bicycle is practically suspended in the air, preventing the bicycle from drifting away. Despite proving its usefulness to cyclists, this device has one major flaw which is the lack of portability. This limiting factor could deter the use of such devices in cases where extra labor is intolerable, leaving them unused. Tackling this issue requires two objectives, developing a bicycle stand offering high portability through a foldability feature and fabricating a bicycle stand that is light and easy to carry anywhere. The methodology for the development process consists of function analysis, sketching, 3D modelling, rendering, and making a prototype. The design selected for the fabricated prototype managed to successfully implement a folding feature that allows the bicycle stand to be converted to a more carriable shape. Moreover, the fabricated bicycle stands are very light, weighing only half a kilogram. The overall size of the stand is also small allowing it to either be carried or stored easily. To conclude, the designed folding bicycle stand has the potential to increase interest and use of bicycle stands among average cyclists.